Properties of some q-Hausdorff matrices - Akgun, F. Aydin; Rhoades, B. E. (ELSEVIER SCIENCE INC, 2013)
In this paper we show that the C-q matrices, the q-Hausdorff analogs of the Cesaro matrix of order 1, are all equivalent to convergence, and that the same is true of the q-Holder matrices. We also show that the C-q matrices of order alpha, for each each positive alpha, are regular. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: q-Cesaro matrices; q-Holder matrices; q-Hausdorff matrices; SUMMATION METHODS; MOMENT SERIES; EQUIVALENCE; SUMMABILITY; Mathematics